1993
DOI: 10.1099/0022-1317-74-11-2419
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new bacteriophage which infects bacteria of the genus Acidiphilium

Abstract: A novel bacteriophage, termed ~bAcl, that infects strains of the genus Acidiphilium (acidophilic, heterotrophic, aerobic, Gram-negative eubacteria) most commonly isolated from acidic mine drainage environments, has been discovered and several of its properties have been determined. This is the first report of a bacteriophage infecting such cells. The virion has a lambdoid morphology and is larger than 2, as shown by electron microscopy and sucrose gradient centrifugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These viruses have proved to be unique in terms of their morphology, which includes tailedspindle, filamentous, polihedral, bottle-, lemon-and droplet-shapes, and also in terms of their life cycles, which span integrated and silent proviruses that parasitize their host, infective and lytic forms that kill the cells they infect, and chronic infecting virions that keep their hosts viable while releasing viral progeny (Wang et al, 2018;Liu et al, 2018;Liu et al 2017;Hochstein et al, 2016;Wang et al, 2015;Dellas et al, 2014). Tailed viruses infecting bacterial extreme acidophiles of the genus Acidiphilium (Ward et al, 1993) and Acidithiobacillus have also been reported (Covarrubias et al, 2018;Tapia et al, 2012).…”
Section: Viruses and Provirusesmentioning
confidence: 99%
“…These viruses have proved to be unique in terms of their morphology, which includes tailedspindle, filamentous, polihedral, bottle-, lemon-and droplet-shapes, and also in terms of their life cycles, which span integrated and silent proviruses that parasitize their host, infective and lytic forms that kill the cells they infect, and chronic infecting virions that keep their hosts viable while releasing viral progeny (Wang et al, 2018;Liu et al, 2018;Liu et al 2017;Hochstein et al, 2016;Wang et al, 2015;Dellas et al, 2014). Tailed viruses infecting bacterial extreme acidophiles of the genus Acidiphilium (Ward et al, 1993) and Acidithiobacillus have also been reported (Covarrubias et al, 2018;Tapia et al, 2012).…”
Section: Viruses and Provirusesmentioning
confidence: 99%
“…Difficulties can, however, arise when the conditions for cultivation are not conducive to the use of standard materials, as is the case with some extreme environments like very high or low temperatures. This overall message should also be borne in mind when isolating phages from other extreme environments not discussed in detail here, such as high salinity (Muruga et al 2013) or high acidity (Ward et al 1993), all of which may need to be considered when choosing media, culture conditions, gelling agent, etc.…”
Section: Isolation From Diverse Environmentsmentioning
confidence: 99%